The Implementation of Politeness Strategy in a Group of Teenagers in Tambak District Banyumas Regency - Arif Nur Wahid, Wahid (Papanda Publisher, 2025)
Abstract This study aims to examine the application of politeness strategies in the daily conversations of teenagers in their hangouts at their friend's house. This study use qualitative method. Language is not just for communication but also crucial for establishing and maintaining relationships in society. People use politeness strategies, such as those proposed by Brown and Levinson, to enhance communication harmony by focusing on maintaining